2014
DOI: 10.1136/bjophthalmol-2014-305376
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomised comparison of probing versus bicanalicular silastic intubation for congenital nasolacrimal duct obstruction

Abstract: Probing for simple CNLDO in young children is adequate. Bicanalicular silastic intubation seems to have a role in achieving successful outcomes in complex CNLDO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 23 publications
0
34
0
3
Order By: Relevance
“…Weitere Studien konnten zeigen, dass der Einsatz von Silikonstützma-terialien bei komplexen Situationen sehr sinnvoll ist. Hierdurch konnte die Heilungsrate von 47-52 % auf 85-91 % gesteigert werden [25,26]. Diese Ergebnisse konnten auch durch unsere Untersuchungen bestätigt werden.…”
Section: Diskussionunclassified
“…Weitere Studien konnten zeigen, dass der Einsatz von Silikonstützma-terialien bei komplexen Situationen sehr sinnvoll ist. Hierdurch konnte die Heilungsrate von 47-52 % auf 85-91 % gesteigert werden [25,26]. Diese Ergebnisse konnten auch durch unsere Untersuchungen bestätigt werden.…”
Section: Diskussionunclassified
“…Five studies were not RCTs (one case series: Chaabouni 1993; one that provided various treatments to patients for NLDO in a particular order in which they only received probing if all previous procedures had failed: Ekinciler 1994; and three that described probing surgery in a narrative format: Hernandez 1967; Ishikawa 1990; Robb 1985). We excluded one study that compared probing to a another surgical procedure (bicanalicular silastic intubation) for treating NLDO (Al-Faky 2015). …”
Section: Resultsmentioning
confidence: 99%
“…After birth, it was shown that more than 30% of infants 11 months and 9.5 years, the overall success rate was 85%, the success rate was 89% for eyes in children with Down syndrome and the success rate was 85% for eyes in children without Down syndrome. Al-Faky et al 20 . reported 207 eyes of 181 children between 1 and 8 years old with CNLDO who had not undergone previous surgical treatment were included in the study.…”
Section: Discussionmentioning
confidence: 99%